Mediated Public Diplomacy Redefined: Foreign Stakeholder Engagement via Paid, Earned, Shared, and Owned Media. (November 2019) - Golan, Guy J.; Manor, Ilan; Arceneaux, Phillip
Mediated public diplomacy literature examines the engagement of foreign audiences by governments via mediated channels. To date, scholars have examined the competitive contest between global rivals in promoting and contesting one another's frames as reflected in global news media coverage. Recognizing the meaningful impact of social media platforms, along with the global rise of government-sponsored media organizations, the current study builds on previous mediated public diplomacy scholarship by expanding the scope of the literature beyond the earned media perspective to also include paid, shared, and owned media. The article presents a revised definition of the term mediated public diplomacy along with a case study of government to foreign stakeholder engagement via the social media platform, Twitter.